Fichte and Gentile - Notes about the relationship between Transcendental Idealism and Actual Idealism - Fusaro, Diego (Revista Ágora Filosófica, 2016)
This essay is to express some considerations about the theoretical relation which bonds the Actual Idealism of Giovanni Gentile to the "system of freedom" concerning the Wissenschaftslehre or 'Doctrine of Science' of Johann Gottlieb Fichte. The Doctrine seems to have rightful claim to be the philosophical system nearest to the Actualistic code, which was to be openly developed by Gentile in the early years of twentieth century, and the seeds of which had already been sewn by the monographic studies dedicated to Rosmini and Gioberti, from one side, and to Marx, from another. The essay discusses the conceptual lineage of Actual Idealism, it's specific links to Doctrine of Science as a critique of Kant and Hegel, and possible reasons for the widely perceived lack of acknowledgement perceptible in the Italian thinker's work.